Advances in Information Technology Third International Conference, IAIT 2009, Bangkok, Thailand, December 1-5, 2009. Proceedings - Papasratorn, Borworn; Chutimaskul, Wichian; Porkaew, Kriengkrai; Vanijja, Vajirasak; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
At the School of Information Technology, KMUTT, we believe that information te- nology is the most important driver of economy and social development. IT can - able better productivity, as well as helping us to save resources. IT is giving rise to a new round of industrial and business revolution. We now can have products and s- vices that once were believed to be beyond reach. Without IT, it is impossible for people to realize their full potential. Businesses worldwide are harnessing the power of broadband communication, which will have a profound and constructive impact on the economic, social devel- ment, education, and almost all aspects of our life. This new era of unified commu- cation presents us with new challenges. This is why we should work together more closely to enhance the exchange of knowledge related to effective application of broadband communication and IT. It is my sincere hope that all contributions to the Third International Conference on Advances in Information Technology (IAIT 2009) will increase our understanding of how we can have effectively apply this emerging technology for the benefit of all people all around the world. I hope IAIT 2009 will also lead to more research that can contr- ute to a better methodology for IT applications in the era of unified communication. I am very grateful to all our keynotes speakers for coming all the way to Thailand.
Performance Analysis of BitTorrent and Its Impact on Real-Time Video Applications -- TOF Depth Camera Based 3D Gesture Interaction System -- Mining Top-K Periodic-Frequent Pattern from Transactional Databases without Support Threshold -- Intercropping Planning Models for an Agricultural Expert System -- An Impact of Scheduling Strategy to Parallel FI-Growth Data Mining Algorithm -- Bringing Precision to Office Document Search by Semantic Relationship Approach -- Multi-objective Optimization for Information Sharing in Vehicular Ad Hoc Networks -- Analysis on Relationships among Software Models through Traceability Activity -- An Axiomatic and Object-Based Approach to Tracing Safety Properties in the Context of ARP 4754 -- Token Traversal Strategies of a Distributed Spanning Forest Algorithm in Mobile Ad Hoc - Delay Tolerant Networks -- Requirements for a Knowledge Transfer Framework in the Field of Software Development Process Management for Executive Information Systems in the Telecommunications Industry -- Automating the Dissemination of Information Entities to Healthcare Professionals -- The Triangular Life Cycle Model -- A Hybrid Technique for Complete Viral Infected Recovery -- Procedurally Placement of Tropical Beach Vegetation in Level Design Tools -- Development and Performance Analysis of Grid Scheduling Algorithms -- Association Rule Mining for Intellectual Capital of Enterprises in Central Region of Thailand -- Attitudes toward Using Communication Technologies in Education: A Comparative Study of Email and SMS -- Study of Factors Influencing Online Auction Customer Loyalty, Repurchase Intention, and Postitive Word of Mouth: A Case Study of Students from Universities in Taipei, Taiwan.
Keywords: Computer science; Computer communication systems; Software engineering; Operating systems (Computers).; Computers; User interfaces (Computer systems).; Computer Science; Software Engineering/Programming and Operating Systems; Computer Communication Networks; Operating Systems; Software Engineering; User Interfaces and Human Computer Interaction; Information Systems and Communication Service; Electronic books